2018
DOI: 10.29252/aassjournal.6.2.55
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Focus Instructions on Dart Throwing Performance in Children With and Without Developmental Coordination Disorder

Abstract: Background. Adults benefit more from external focus than internal focus when performing motor skills. Objectives. The aim of this study was to investigate the effects of internal and external focus of attention on dart throwing performance in children with and without developmental coordination disorder. Methods. Twenty men, 20 normal boys and 20 boys with developmental coordination disorder were selected by Motor Observation Questionnaire for Teachers. The task was to throw the darts to the target which was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Yet, visual information did not mediate EF benefits in adults and adolescents with severe visual impairment in discrete, locomotion and maximal velocity tasks respectively (Abdollahipour et al, 2019;McNamara, et al, 2019 2 ). These findings further suggest that age, motor experience, task type and focus preference/familiarity may have a more profound influence on children's motor learning in comparison to the role of acquiring key visual information (Fathi Khatab et al, 2018;McNamara et al, 2017;McNamara et al, 2019;Maurer & Munzert, 2013;Wulf et al, 2001). Additionally, task difficulty may moderate effort perceptions and the benefits of an EF in children with cerebral palsy, but an EF is generally effective under constant practice conditions (Pourazar et al, 2017).…”
Section: Other Lines Of Research With Optimal Variablesmentioning
confidence: 92%
See 4 more Smart Citations
“…Yet, visual information did not mediate EF benefits in adults and adolescents with severe visual impairment in discrete, locomotion and maximal velocity tasks respectively (Abdollahipour et al, 2019;McNamara, et al, 2019 2 ). These findings further suggest that age, motor experience, task type and focus preference/familiarity may have a more profound influence on children's motor learning in comparison to the role of acquiring key visual information (Fathi Khatab et al, 2018;McNamara et al, 2017;McNamara et al, 2019;Maurer & Munzert, 2013;Wulf et al, 2001). Additionally, task difficulty may moderate effort perceptions and the benefits of an EF in children with cerebral palsy, but an EF is generally effective under constant practice conditions (Pourazar et al, 2017).…”
Section: Other Lines Of Research With Optimal Variablesmentioning
confidence: 92%
“…Buszard et al, (2017) stated that complex and detailed instructions negatively impact children's motor performance by overloading their relatively limited working memory capacity. In contrast, concise EF instructions have enhanced motor performance and learning across the full FMS range, presumably due to their limited impact on attentional resources in comparison to an IF (e.g., Bodasinska, Zielinski, & Makaruk, 2019;Chiviacowsky, Wulf, & Ávila, 2013;Fathi Khatab et al, 2018;Kal, van der Kamp, & Houdijk, 2013;Marchant, Griffiths, Partridge, Belsley, & Porter, 2018;Wulf, 2013). However, Patranek, Bolter andBell (2019) found that concise IF feedback (e.g., arms out wide), when delivered intermittently, enhanced movement form when learning an overhand throw in comparison to EF feedback (e.g., make a "T"; table 4).…”
Section: Developmental Factors and Task Constraintsmentioning
confidence: 99%
See 3 more Smart Citations